Acute toxicity study of a new dibenzofuran oxime derivative GIZH-272 in mice - S. V. Alekseeva; A. V. Sorokina; A. V. . Volkova; I. A. Miroshkina; K. S. Kachalov; I. V. Alekseev; A. D. Zakharov; A. D. Durnev (Фармакокинетика и Фармакодинамика, 2024)
Relevance. Acute toxicity testing is a common procedure for preclinical safety testing of potential agents. The purpose of this study was to study the acute toxicity of the compound GIZH-272, a new dibenzofuran oxime derivative with anti-ischemic and anticonvulsant effects. Methods. The compound was administered to mice intraperitoneally and orally once. Within 14 days, the condition of the animals was monitored, clinical manifestations of intoxication were recorded, and changes in the dynamics of body weight and its growth were recorded. Results. It was found that the test compound at maximum doses did not lead to the death of mice. Therefore, the data obtained according to the classification of Sidorov K.K. (1973), make it possible to attribute GIZH-272 to the 5th class of toxicity — "practically non-toxic substance". In accordance with GOST 12.1.007-76, the GIZH-272 compound belongs to the 4th hazard class (low-hazard substance) for oral administration.